2022
DOI: 10.3389/fpubh.2022.976188
|View full text |Cite
|
Sign up to set email alerts
|

Does increasing public expenditure on sports promote regional sustainable development: Evidence from China

Abstract: In the post-COVID era, how to improve the level of regional sustainable development has attracted much attention. And the vigorous development of the sports economy may be closely related to the regional sustainable development. This paper explores the impact and mechanism analysis of government sports public expenditure on regional sustainable development from the perspective of sports economic development. The study found that China's sustainable development presents obvious ladder-like characteristics and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Improving the level of technological innovation is conducive to improving energy efficiency, which leads to a reduction in carbon emissions. Wang et al (2020) found that an improvement in the technological level can reduce the cost of carbon emission reduction through the learning effect [31]. (4) Environmental regulation (Env) is measured by the ratio of total investment in pollution control to GDP.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the level of technological innovation is conducive to improving energy efficiency, which leads to a reduction in carbon emissions. Wang et al (2020) found that an improvement in the technological level can reduce the cost of carbon emission reduction through the learning effect [31]. (4) Environmental regulation (Env) is measured by the ratio of total investment in pollution control to GDP.…”
Section: Control Variablesmentioning
confidence: 99%
“…(3) In view of the spillover effect of the digital economy on the carbon emission reduction of the sports industry, the government should promote the construction of the integrated layout of digital infrastructure and give full play to the radiating role of the digital economy. It is necessary to build an integrated digital infrastructure layout by increasing the coordination of new infrastructure construction in various regions [31]. At the same time, it need to promote the cross-regional division of labor and cooperation, improve the breadth and depth of the integration of information technology and the real industry, and fully release its spatial contribution to the green transformation of the industry.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Research on regional sustainable development mainly explores areas such as land resources and environmental protection [ 28 , 29 ], industrial and economic development [ 30 , 31 ], government institutional mechanisms [ 32 ], and transportation and infrastructure [ 33 , 34 ]. Recently, some scholars have paid attention to the spatial distribution differences of cities’ sustainable development degree in the region and the driving effects of regional sustainable development [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…By integrating these components, the PSR model aims to optimize athletes' psychological resources, enhance their performance consistency, and promote mental toughness in competitive sports contexts [3]. Through targeted interventions and individualized coaching, athletes can cultivate these skills to unlock their full potential and achieve peak performance in their respective sports [4]. Sports venues integrating the Psychological Skills Model (PSR) represent a dynamic shift towards comprehensive athlete development and spectator experience.…”
Section: Introductionmentioning
confidence: 99%